RELASI KUASA BALADIKA BALI DENGAN CALON KEPALA DAERAH DALAM PEMILU KABUPATEN BADUNG TAHUN 2015 - Alit Astikayana, Ida Bagus; Ali Azhar, Muhammad; Bandiyah, Bandiyah (Jurnal Nawala Politika, 2019)
ABSTRACT The purpose of this study is to determine the relationship that occurs between Baladika Bali with Giri Prasta as a candidate for the head of Badung area 2015. The study used qualitative methodology with qualitative descriptive. Primary data were collected by purposive sampling interview technique, and secondary data were obtained from news articles and other matters related to the research. This study uses the theory of power relations proposed by Foucault. The findings obtained in this study are most of the victory of Giri Prasta due to the relationship that occurred between Giri Prasta Baladika Bali organization. Many advantages obtained Baladika Bali, the first Gus Bota who get a position in the PDIP party as deputy chairman of DPC Badung. Both brothers from Gus Bota, Gus Ari get the position as chairman of the PDI-P wing organization. Keywords:Relation, Community Organization, Prospective Head of Region